Sentiment Analysis of Reddit Comments about Israel-Palestine Conflict Following the October 2023 Escalation - Jan Gawroński (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This researches analyzes the sentiment of Reddit comments regarding the Israel-Palestine conflict during the first two months following the October 7, 2023, escalation. Social media which plays a critical role in shaping public perception and discourse on geopolitical events making sentiment analysis a valuable tool for assessing online reactions. Using the pre-collected dataset “Daily Public Opinion on Israel-Palestine War” from Kaggle, which contains 389,229 comments from 14 subreddits, this study applies the VADER sentiment analysis tool within Python’s pandas environment. VADER's lexicon, optimized for social media text, enables the assessment of comment polarity (positive, neutral, negative) and overall sentiment valence. The findings suggest a correlation between short-term sentiment fluctuations and widely publicized events in the Israel-Hamas war, indicating that online discourse reacts dynamically to developments on the ground. This study contributes to applied linguistics in understanding how natural language in digital communities emotionally respond to real-world conflicts.